OPTIMALISASI KINERJA GURU MELALUI SUPERVISI TERHADAP PENINGKATAN PEMBELAJARAN MATEMATIKA; STUDI KASUS SD NGESREP 01 SEMARANG - ermin ermin (Universitas Muhammadiyah Semarang, 2020)
Supervision; observe, supervise / guide and stimulate activities. Activities carried out by others with a view to making improvements through the selection of teaching tools and better teaching methods, ways of systematic assessment of the whole phase of the teaching process. The quality of education is influenced by many components, there are three main components that are interrelated and have a strategic position in teaching and learning activities. The three components are the curriculum, the teacher and the student, the teacher occupies a central position because its role is crucial considering that in learning a teacher must be able to translate the values contained in the curriculum optimally. The aim is to improve student learning outcomes by experimenting with class action and supervision. The results of the study there are significant differences between the VA class and Class VB p / value less than 0.05 and there is an influence between planning, implementation and assessment according to the results of optimization analysis.